1982
DOI: 10.1002/pssa.2210700125
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of the EBIC contrast of dislocations in silicon

Abstract: EBIC contrast measurements of individual surface‐parallel dislocations lying in the p‐region of a planar silicon diode and TEM analysis are correlated in order to study the EBIC contrast behaviour of dislocations of different type. The experimental results are in good agreement with theoretical predictions. In particular, it is possible to classify the dislocations with respect to their type by the real strength of the recombination activity. The surface recombination velocity and the minority carrier diffusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…They are basically rows of dislocations and are by some authors attributed to dislocations and by others to GBs. The recombination behavior of different types of single dislocations in Si was revealed for instance in [43] and [47], and the impact of the density of dislocations on the recombination activity was shown, e.g., in [48], mostly by electron beam induced current (EBIC) investigations. The results of these investigations were that clean dislocations (i.e., without impurity atoms) are not recombination active at room temperature (RT), only contaminated dislocations may be harmful.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They are basically rows of dislocations and are by some authors attributed to dislocations and by others to GBs. The recombination behavior of different types of single dislocations in Si was revealed for instance in [43] and [47], and the impact of the density of dislocations on the recombination activity was shown, e.g., in [48], mostly by electron beam induced current (EBIC) investigations. The results of these investigations were that clean dislocations (i.e., without impurity atoms) are not recombination active at room temperature (RT), only contaminated dislocations may be harmful.…”
mentioning
confidence: 99%
“…In the same publication, it was shown that nearly all GB types might be recombination active if they are heavily contaminated by impurities. In [47], CZ-grown Si with defects was used as model material, and in [43], the model structures have been produced artificially by epitaxial growth of Si and Si-Ge layers on an n + -type (100) Si substrate. Different authors found that particularly SAGBs (tilt angle between approximately 1°a nd 3°) in mc-Si are recombination active, especially if they are decorated by Fe impurities, but no detailed investigation of the SAGBs, i.e., their crystallographic structure, was shown [44], [50]- [52].…”
mentioning
confidence: 99%
“…1͔ should be independent of the defect depth, whereas both theory and experiment indicate that the contrast depends on the defectjunction distance. 7 Moreover, Eq. ͑1͒ foresees vanishing contrast for a defect lying deeper than the generation volume, since in this case ⌬z(x)ϭ0; this conclusion is contradicted by experimental EBIC images and related simulations.…”
Section: ͓S0003-6951͑97͒05041-9͔mentioning
confidence: 99%
“…15 The number of misfit dislocations per dark line can be estimated by using high resolution techniques like transmission electron microscopy. 14 However, it has been shown that the recombination strength of individual dislocations varies considerably with structural parameters like the Burgers vector 18 or as a consequence of impurity segregation at the dislocation core. 15 A detailed analysis of the recombination strength, related to the observed dark lines for different levels of strain relaxation, is currently under investigation and will be the subject of a forthcoming paper.…”
Section: Samples and Experimentsmentioning
confidence: 99%